Atypical Presentation of Lateral Periodontal Cyst in an Elderly Female Patient - A Rare Case Report - Renita Lorina Castelino; Kumuda Rao; Supriya Bhat; Subhas Gogineni Babu (Faculty of Dentistry, Universitas Indonesia, 2016)
The lateral periodontal lateral cyst (LPC) is a uncommon developmental odontogenic cyst defined as a radiolucent lesion which develops along the lateral aspect of an erupted vital tooth. LPC represents approximately 0.8% to 2% of all odontogenic cysts .The most frequently reported location of a lateral periodontal cyst is the mandibular canine premolar area, followed by the anterior region of the maxilla. Lateral periodontal cyst is usually asymptomatic and presents as a round, oval or teardrop-like well-circumscribed interradicular radiolucent area, usually with a sclerotic margin lying between the apex and cervical margin of the teeth . The lateral periodontal cyst usually is seen in the fifth to sixth decade of life with a male preponderance. This paper reports an unusual and an atypical case of an inter radicular radiolucent cystic lesion in located between the mandibular central incisor and canine area in an 87 year old female patient mimicking clinically and radiographically as an residual cyst but histopathologically confirmed as an lateral periodontal cyst. DOI: 10.14693/jdi.v23i1.967